Tracking the parallelism of difference with ostension schemes. (July 2017) - Werner, Tom
Abstract: In this paper I develop an instrument for monolingual elicitation through ostension. I call the instrument an ostension scheme . Ostension schemes are matrices with rows to introduce pictures and columns to represent sentences. Ostension schemes have utility for monolingual elicitation of an unfamiliar language and they allow for the collection and storage of certain kinds of linguistic data in a particularly transparent fashion that does not primarily utilize translation. This transparency is due to design features which help distinguish between a sentence and its entailments or between a sentence and precizations of that sentence. The data stored on an ostension scheme allows access to the linguistic hierarchy at the level of the basic sentence. Comparison of minimal sentence pairs allows for movement within the linguistic hierarchy, from the level of the basic sentence to the level of the morpheme or the phoneme. Ostension schemes utilize a principle I call the parallelism of difference . By this principle, minimal differences in the forms of basic sentences tend to correspond to minimal differences in situations described by these sentences. I take up the problem of how to determine these minimal differences. I demonstrate how ostension schemes have been used to elicit a number of sentences from the Sakha language (Yakut) and to identify morphemes in the language, and I also provide a brief discussion of overcoming first language bias of the designer of the scheme. Finally, I consider how the rows and columns of ostension schemes interact and how this interaction facilitates elicitation. The instrument as developed here promises to be highly practical, but at the same time it is limited in the kind of language it can be used to elicit. The theoretical investigation should be useful not only by engaging in fundamental issues of language study but also by paving the way for possibly broader applications of these ostension schemes. Highlights: A systematic approach to ostension, the ostension scheme, is reviewed. Sentences are distinguished from their entailments and from their precizations. Access is gained to the linguistic hierarchy at the level of the basic sentence. Tracking the parallelism of difference is used to move within the hierarchy. The connection between information and linguistic meaning is explored.